2018
DOI: 10.26740/jrpd.v4n3.p789-799
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Komik Berbasis CTL Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar

Abstract: The research aims to develop and test the validity, practicality, as well as the effectiveness of learning media, that is comic media based on Contextual Teaching And Learning (CTL) on Social Science subject. Observation model used is the research and development model (R&D) of Borg and Gall. The result of this research shows that comic media based on CTL is reasonable, practical and effective. The using of comic media based on CTL gives influence to the learning result of student. It can be seen through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…However, material that is directly related to real life can be made easily with the storyline, for example number material can be made using comic media because the concepts are many and often encountered in everyday life (Agoes Prihanto & Nova Hasti Yunianta, 2018;Kurniawan et al ., 2015). Science and social materials are certainly easier to find in everyday life because the concepts are often found in real life (Ais Rosyida, 2019;Ariesta & Kusumayati, 2018;Sardone, 2017).…”
Section: Selection Of Important Topics In Learning Using Comic Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…However, material that is directly related to real life can be made easily with the storyline, for example number material can be made using comic media because the concepts are many and often encountered in everyday life (Agoes Prihanto & Nova Hasti Yunianta, 2018;Kurniawan et al ., 2015). Science and social materials are certainly easier to find in everyday life because the concepts are often found in real life (Ais Rosyida, 2019;Ariesta & Kusumayati, 2018;Sardone, 2017).…”
Section: Selection Of Important Topics In Learning Using Comic Mediamentioning
confidence: 99%
“…Keep in mind that an interesting storyline will give an interesting impression on students. Character selection also needs to be adapted to elementary school students (Ais Rosyida et al, 2018;Sukmanasa et al, 2017a). This can have bad results if the characters displayed are not in accordance with the character of students in elementary school.…”
Section: Selection Of Important Topics In Learning Using Comic Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Pembelajaran berbasis komputer itu sendiri merupakan suatu bentuk pembelajaran yang menjadikan komputer sebagai piranti sistem pembelajaran individual, di mana siswa dapat berinteraksi langsung dengan sistem komputer yang sengaja dirancang atau dimanfaatkan oleh guru (Smaldino et al, 2001). Siswa, khususnya dalam usia belajar tingkat sekolah dasar, juga akan lebih bersemangat dan meningkatkan hasil belajar ketika media belajar yang digunakan oleh guru menarik secara visual (Rosyida, 2019). Dalam pengertian tersebut dapat dipahami bahwa posisi dan peran seorang guru sangatlah penting.…”
Section: Pendahuluanunclassified
“…The success of integrating comic media with the learning approach can be seen from previous research conducted by Ais Rosyida, Mustaji, and Waspodo Tjipto Subroto showed that CTL-based comic media is feasible, practical and effective to improve learning outcomes of third grade students of elementary schools in social studies subjects [12]. Even Ade Irma S. in his research showed that Advances in Social Science, Education and Humanities Research, volume 384 comic media with role playing affect the results and students' interest in learning about virus material.…”
Section: Introductionmentioning
confidence: 99%